2022
DOI: 10.1177/23259671221120662
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Open Versus Arthroscopic Repair for Subscapularis Tendon Tears With or Without Concomitant Supraspinatus Tendon Tears

Abstract: Background: The literature comparing open and arthroscopic repair of subscapularis tendon (ST) tears is insufficient. Purpose: To compare the clinical results of open versus arthroscopic repair of ST tears with or without concomitant supraspinatus tears. Study Design: Retrospective cohort study. Methods: We retrospectively evaluated 70 patients treated for isolated ST tears and ST tears with concomitant supraspinatus tendon tears at a single center between 2011 and 2019. Patients were divided into 2 groups: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 44 publications
3
5
2
Order By: Relevance
“…Isolated SSC tears are relatively rare compared with posterosuperior cuff tears, and there is limited research on isolated SSC repairs in the literature. 1 , 32 , 36 , 37 Since the study by Burkhart and Tehrany 5 on AISR, subsequent studies have consistently demonstrated significant improvements in PROs and ROM, 4 , 14 , 16 , 24 , 34 which align with the findings from our study. Among previous studies, Seppel et al 38 and Liu et al 28 presented long-term outcomes after the repair of isolated SSC tears, with mean follow-up times of 98.4 and 120 months, respectively, while our study presents midterm follow-up results (56.7 ± 3.3 months) in the largest sample size 36 , 37 , 41 of patients (N = 77).…”
Section: Discussionsupporting
confidence: 90%
“…Isolated SSC tears are relatively rare compared with posterosuperior cuff tears, and there is limited research on isolated SSC repairs in the literature. 1 , 32 , 36 , 37 Since the study by Burkhart and Tehrany 5 on AISR, subsequent studies have consistently demonstrated significant improvements in PROs and ROM, 4 , 14 , 16 , 24 , 34 which align with the findings from our study. Among previous studies, Seppel et al 38 and Liu et al 28 presented long-term outcomes after the repair of isolated SSC tears, with mean follow-up times of 98.4 and 120 months, respectively, while our study presents midterm follow-up results (56.7 ± 3.3 months) in the largest sample size 36 , 37 , 41 of patients (N = 77).…”
Section: Discussionsupporting
confidence: 90%
“…They observed that the side impacted was substantially different among both groups (Pvalue 0.007), which was contrary to our observations. They noted that tendon tear was considerably different among both studied groups; isolated were substantially lower in AS than open group (1:7) but combined were considerably higher in AS than open group (35:27) (P-value = 0.026) [13] .…”
Section: Discussionmentioning
confidence: 94%
“…In 1954, Hauser conducted the initial investigation into ST repair. Despite the fact that ST injuries have been documented historically, there aren't many studies on how to treat them because to the tendon's proximity to vital neurovascular systems and its lower risk of injury compared to the other tendons that make up the rotator cuff [13] .…”
Section: Discussionmentioning
confidence: 99%
“…However, whether it would be helpful to repair the SSC tear is not clear, since most of the patients were combined with supraspinatus and infraspinatus tendon tears in our series [36, 37]. InSSC tears might be the cause of unexplained anterior shoulder pain [36, 38, 39].…”
Section: Discussionmentioning
confidence: 99%